Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.2147/jir.s253980
|View full text |Cite
|
Sign up to set email alerts
|

<p>The IL-33/sST2 Axis in Thromboangiitis Obliterans</p>

Abstract: Background: Until recently, it remains unknown whether thromboangiitis obliterans (TAO) is a type of systemic vasculitis. A high level of IL-33 and its soluble decoy receptor sST2 in the acute phase of systemic vasculitis has been demonstrated. Methods: The serum level of IL-33 and sST2 in 50 TAO patients, 20 age-and smoking habit-matched controls and 19 age-matched non-smoker controls was evaluated. Results: The mean level of IL-33 in TAO, smokers and non-smokers was 370.2±61.7ng/ mL,132.14±2.6ng/mL and 11.3±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…While sST2 is a subtype of ST2, as a decoy receptor, it can be secreted to the outside of the cell and is highly expressed during Evidence-Based Complementary and Alternative Medicine inflammation and oxidative stress damage. It can affect the increased activation of vascular endothelial growth factor receptor and exposure to vascular endothelial tissue, and it can promote coronary artery disease [29,30]. sST2 binds to its specific ligand IL-33 to activate the IL-33/ST2L signaling pathway, which is considered to be a mechanical activation system.…”
Section: Discussionmentioning
confidence: 99%
“…While sST2 is a subtype of ST2, as a decoy receptor, it can be secreted to the outside of the cell and is highly expressed during Evidence-Based Complementary and Alternative Medicine inflammation and oxidative stress damage. It can affect the increased activation of vascular endothelial growth factor receptor and exposure to vascular endothelial tissue, and it can promote coronary artery disease [29,30]. sST2 binds to its specific ligand IL-33 to activate the IL-33/ST2L signaling pathway, which is considered to be a mechanical activation system.…”
Section: Discussionmentioning
confidence: 99%
“…All articles were patient-based and 7 articles were conducted in Iran, 4 in China and one in Korea. Systematic reviews and metaanalyses were not available, all clinical trials were not ethically prohibited, and randomized trials were assessed based on Consort checklists (11,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Results and Ndingsmentioning
confidence: 99%
“…On the other hand, it may be helpful if TAO is an autoimmune disease. The results of the investigations showed that the regulation pattern of IL-33/sST2 in TAO is different from that in autoimmune vasculitis such as SLE (19). Th17 cells are a subset of T helper cells that play a key role in in ammation by activating neutrophils.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, high serum levels of IL-17, -22, -23, and -33 and low IL-10 have been reported in TAO compared to smoker controls [14,86,87].…”
Section: Cytokinesmentioning
confidence: 96%
“…Until recently, TAO is not known as a systemic vasculitis, and it is still unknown whether it is an autoimmune disorder [86,87]. However, the existence of several autoantibodies in some TAO patients has been reported, including anti-endothelial cell antibody (AECA), anti-elastin, and anti-collagen I and III antibodies [99][100][101][102].…”
Section: Autoantibodiesmentioning
confidence: 99%